2014
DOI: 10.1111/jdv.12441
|View full text |Cite
|
Sign up to set email alerts
|

Loss‐of‐function mutations in the gene encoding filaggrin underlie a Japanese family with food‐dependent exercise‐induced anaphylaxis

Abstract: These results indicate that FLG mutations might be involved in the pathogenesis of WDEIA in the present case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…To the best of our knowledge, there have been only a few reports describing clinical features of patients with compound heterozygous FLG mutations . Our present results suggest that patients with bi‐allelic FLG mutations do not always have severe AD.…”
Section: Discussionsupporting
confidence: 49%
“…To the best of our knowledge, there have been only a few reports describing clinical features of patients with compound heterozygous FLG mutations . Our present results suggest that patients with bi‐allelic FLG mutations do not always have severe AD.…”
Section: Discussionsupporting
confidence: 49%
“…There is increasing evidence that an epidermal barrier defect may play an important role. Loss-offunction mutations in the gene encoding filaggrin, a key epidermal protein in skin barrier function, are known to be significant predisposing factors for the development of atopic diseases such as eczema, asthma, and rhinitis [69] and might also be involved in the pathogenesis of WDEIA [70].…”
Section: Pathomechanismmentioning
confidence: 99%
“…There are two contradicting reports showing wheat-dependent exercise-induced anaphylaxis (WDEIA) in a patient without filaggrin mutation and an association of mutation in the filaggrin gene with WDIEA in a Japanese family [65,66]. The available evidence showed that C3H/Hej and Balb/c mice strains have different susceptibilities to gliadin-induced allergy, suggesting genetic control of the disease [30].…”
Section: Insights In To the Molecular Mechanisms Of Wheat Allergenmentioning
confidence: 99%